Providing a Model for Predicting the Financial Behavior of Investors in the Iranian Stock Market - Sallar Ashqi Kareem (Eurasian Journal of Management & Social Sciences)
The pattern of investor behaviour in the stock market is a complex process that is influenced by many factors such as Personality, culture, behavioral patterns, emotional and cognitive biases. The purpose of this study is to provide a model for predicting the financial behavior of investors in the Iranian stock market. In order to achieve the objectives of this study, the necessary data were collected in a time period during the 2019-2020 spring.  Then fuzzy analysis method was used to analyze the data. The results showed that the self-attribution criterion with a weight of 0.107 is in the first priority, the criterion of remorse with a weight of 0.099 is in the second priority and finally the criterion of increasing risk with a weight of 0.094 is in the third priority.